ANALISIS PERAN DIGITAL INFLUENCER DAN STRATEGI KONTEN SOSIAL MEDIA DALAM MEMBANGUN BRAND AWARENESS PRODUK SKINCARE DIKALANGAN GENERASI – Z - MAWIH; Tri Sanatha Wahyu Akbar; Umban Adi Jaya (MBA Journal – Management, Business Administration, and Accounting Journal, 2025)
Indonesia's local skincare industry is experiencing rapid growth amidst intense market competition, making brand awareness a major strategic challenge, particularly in reaching Generation Z, which has unique digital consumption characteristics. This study aims to analyze the influence of digital influencers and social media content strategies on building brand awareness of local skincare products among Generation Z. The research approach used is quantitative associative causality. Data was collected thru an online questionnaire distributed to 373 Generation Z respondents (aged 18-26) in major urban areas of Indonesia. The research variables consist of the role of digital influencers, social media content strategy, and brand awareness. Data analysis was conducted using Structural Equation Modeling (SEM) techniques with the assistance of IBM AMOS software version 26. The results of this study indicate that Digital Influencers do not have a significant influence on Brand Awareness, even tho the indicators used reflect aspects of expertise, credibility, attractiveness, and the ability to influence the audience. Similarly, Content Strategy, measured thru educational value, creativity, visual quality, interactivity, and content consistency, also does not show a significant influence on Brand Awareness